Multifunctional Coumarin-Derived Metal Complexes: Synthesis, Bio-Screening, and In Silico Target Evaluation - Shahid, Zulfiqar Ali; Tabassum, Rukhsana (Universitas Gadjah Mada, 2026)
Antibiotic resistance and oxidative stress-related diseases are emerging as serious global health concerns. These challenges underscore the urgent need for novel, effective, and environmentally friendly therapeutic agents. Coumarin derivative (ZL) and its Mn(II) and Zn(II) metal complexes were synthesized. Structural characterization was performed using various analytical techniques, including FTIR, XRD, 1H-NMR, 13C-NMR, TGA, and MS. FTIR spectra confirmed the existence of the –N=N– functional group of the coumarin-derived ligand. The antioxidant potential of the coumarin-derived compounds (against DPPH and NO) was evaluated. The ZL exhibited the most potent activity, with IC50 values of 6.48 μg/mL for the DPPH assay and 6.91 μg/mL for the NO radical scavenging assay. Antibacterial activities were evaluated against both Gram-negative and Gram-positive bacteria. Molecular docking studies further supported the biological potential of Zn-ZL, which showed strong binding affinities to oligo-1,6-glucosidase (PDB ID: 3AJ7) and mannosyl-oligosaccharide glucosidase (PDB ID: 4J5T), with binding energies of −8.5 and −9.4 kcal/mol, respectively. These findings revealed the therapeutic potential of coumarin-derived compounds and their metal complexes, particularly in addressing oxidative stress and antibiotic resistance.